O processo de luta e implantação da escola família agrícola do bico do papagaio padre Josimo (EFABIP) em Esperantina-TO - Cardoso, Natália da Silva Sousa (Universidade Federal do Tocantins, 2020)
In this monograph, we analyze the process of struggle and implementation of the AgriculturalFamily School of Bico doPapagaio Padre Josimo (EFABIP)in Esperantina, state of Tocantins. For that, we sought to understand how the historical process of struggle for land and agrarian conflicts took place in the micro-region of Bico do Papagaio, the mobilization of social movements in the struggle for a school for the rural peoples of the region to understand aspects of the historical trajectory of the EFABIP. The research is situated within the scope of RuralEducation, being the study of qualitative approach and of bibliographic and documentary nature.In addition to field-school documents, the corpus includes four interviews with social actors in the community, who know how the process of strugglefor land in themicro-region ofBico do Papagaio took place, as well as the creation of the EFABIP. Considering that the number of researches related to the implementation/creation of EFABIP is still reduced, the development of the research emphasizes the struggle and difficulties of the peasants to create anAgricultural Family School in the micro region of Bico do Papagaio.The investigation revealed that the process of struggle for land in this region was very tense for the peasants, because it was a period of many conflicts and deaths. The results also contribute to remembering this history of struggle for land and also the struggle to create an Agricultural Family School, so that this generation can know and understand the long journey that many people have gone through, so that today others can reap the fruits,innocent people have died in the struggle for better lives, but today other people can enjoy these achievements, and EFABIP is making a significant contribution to the training of many peasants, sons and daughters of family farmers.